Women in Neurosurgery: Historical Path to Self-Segregation and Proposal for an Integrated Future - Garozzo, D.; Rispoli, R.; Graziano, F.; Gerardi, R. M.; Grotenhuis, A.; Jenkins, A.; Sammons, V.; Visocchi, M.; Pinazzo, S.; Lima, R.; Martinez, F.; Emamhadi, M.; et al. (Frontiers in Surgery, 2022)
Despite the rising percentage of women accessing the medical profession over the last few decades, surgical specialties are still largely male-dominated; in particular, a remarkable gender disparity is evident in neurosurgery, where only 19% of practitioners are females. Although women may be reluctant to choose a challenging specialty like neurosurgery due to concerns on how to balance family and career, it must be admitted that prejudices against female neurosurgeons have been deeply rooted for long, prompting many to give up and switch track to less demanding subspecialties. Among those that have persisted, many, if not most, have experienced difficulties in career progression and received unequal treatment in comparison with their male counterparts. In 1989, a group of 8 female neurosurgeons founded Women in Neurosurgery (WINS), an organization that aimed to guarantee inclusivity in neurosurgery, promoting a better and more egalitarian working environment. Thereafter, WINS sessions were regularly promoted at international conferences, offering female neurosurgeons a platform to report issues related to gender discrimination. Over the last several years, the mission of WINS sessions in national and international conferences has taken an unexpected deviation; they have progressively become supplementary scientific sessions with only women neurosurgeons as speakers, thus paving the road to a form of self-segregation. This tendency has also resulted in the establishment of sections of only female neurosurgeons within some national societies. Although there remains a faction that fiercely supports the WINS mindset of reserved spaces for women, such segregation is an upsetting prospect for those who deeply believe that science and professionalism have no gender; a growing part of the global neurosurgical community believes that the conception of a “female neurosurgery” and a “male neurosurgery” is misguided and counterproductive and consider the existence of the WINS as anachronistic and no longer necessary.